Kelahiran Baru Di Dalam Kristus Sebagai Titik Awal Pendidikan Karakter Unggul - David Eko Setiawan (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2019)
David Eko Setiawan, Superior character education is a conscious and planned effort that aims to internalize moral values, character which materialized in the implementation of good attitudes and behavior. To achieve these goals, it is necessary to think of an important event that must occur in human life. The event is called new birth. New birth is a spiritual event that can only be done by God through the Holy Spirit to people who believe in the preaching of the gospel. When the event occurs, God will give him a new life. At that time the old nature will be replaced with a new nature so that believers could be able to express a new life. The correlation of the new birth with superior character education is through new birth individuals experience very significant changes. These changes touch aspects such as mind, feeling and will so that one can have superior qualities in him. This is the key to radical change in a person so that eventually he can have a superior character